Data Collection of Students' Social Relationships with Sociometry and Its Implications for Improving Interpersonal Skills in Counseling Services - Irman Irman; Tuti Yamila Sari (International Journal of Research in Counseling, 2022)
Students' Social Contact Is One Of The  Problems That Are Often Faced In Schools.  The Relationship Is Related To Social Relations With Friends And Social Relationships With Teachers. The Purpose Of Writing This Article Is To Reveal Empirical Data Related To The Data Collection Of Students' Social Relations With Sociometric Instruments And Their Implications For Improving Interpersonal Skills In Counseling Services. The Research Was Conducted Through A Classroom Action Research Approach. The Research Instrument Is The Application Of Sociometry. The Respondents To The Study Were 32 High School X Students. The Research Data Is Processed Based On Quantitative Sociogram Data. The Resultsshowed That In The Classroom There Were 9 Isolated Students, 4 Popular Students And 17 Students Chose Each Other.  To All Students In The Class Are Provided With Classical Guidance Services, As Many As 2 Cycles.  In The First Cycle, Classical Guidance Services Are Provided With Storytelling Materials In Front Of The Class. In This First Cycle It Is Seen That Of The 32 Students The Interpersonal Level Of His Skills Is In The Category , While The Other Four People Are Still Isolated. In The Second Cycle, Based On Observations, Already All Six Isolated Students Can Blend In The Classroom. Based On The Results Of This Study, It Can Be Concluded That Data On Social Relations In The Classroom Can Be Drawn Through Sociometric Instruments, Based On These Data Can Be Provided Classical Guidance Services To Improve Interpersonal Skills.